Successful Use of Peripheral Nerve Blocks as the Primary Anesthetic in High-Risk Patients Undergoing Hip Surgery: A Case Series. Issue 1 (January 2021) - Bryan, Andre; Montilla, Elilary; Steinberg, Sofia; Farah, Fadi; Muse, Iyabo O.
Abstract : The incidence of hip fractures in the United States is increasing as the population ages. Elderly patients are more likely to have extensive comorbidities, which contribute to long-term consequences after a hip fracture. These patients often experience permanent disability, restrictions in activities of daily life, higher rates of depression, cardiovascular disease, and mortality rate. The authors describe a combination of peripheral nerve blocks to provide surgical anesthesia for corrective hip surgery in 5 high-risk patients.